Traumatic Experience of the Great War and Obstacles to Recovery in Virginia Woolf’s Mrs. Dalloway - GUEMIDA ,Manel; BENELMOUAZ, Fatima Zohra; GUELLIL, Assia (Faculty of Letters and Foreign Languages Department of English, 2017)
The modernist novelist Virginia Woolf was among the first writers to deal with the psychological aftermath of the First World War in post-war British society particularly in her fourth novel Mrs. Dalloway. The present study examines the traumatic experience of the shell-shocked character Septimus Warren Smith. This study attempts to describe the hysteric symptoms, possible causes and treatment of the trauma and psychological loss as portrayed in both the literature and the medicine of that time. Hence, this work adopts two main theories: Freudian trauma theory and Contemporary trauma theory in order to analyse and diagnose Septimus’ traumatic experience of the Great War, and to see how these trauma theories could work properly in discovering the various kinds of traumas and psychological losses in Woolf’s novel. The main findings of this work are that it is too hard for the survivor to integrate himself into normal life especially who suffered from traumatic experience. In Mrs. Dalloway, the traumatized characters can be successfully associated with trauma studies especially for Clarissa and Septimus. The novelist and the two characters share some common perspectives particularly Septimus, who becomes her double. Thus, the novel can be stand to highlight the influence between literature and medicine particularly in psychology. Consequently, she contributes to add special perspectives in literature of trauma